Comparison of Health Service Utilization for Febrile Children Before and After Introduction of Malaria Rapid Diagnostic Tests and Artemisinin-Based Combination Therapy in Rural Papua New Guinea - Tsukahara, Takahiro; Sugahara, Takuma; Furusawa, Takuro; Hombhanje, Francis Wanak (Frontiers in Public Health, 2018)
Background: In Papua New Guinea (PNG), a malaria treatment policy using rapid diagnostic tests (RDTs) plus artemisinin-based combination therapy (ACT) was widely introduced to rural communities in 2012. The objectives of the study were to evaluate the effect of this RDT/ACT introduction to a rural PNG population on health service utilization and to compare factors associated with health service utilization before and after the RDT/ACT introduction. Methods: Household surveys with structured questionnaires were conducted before and after the introduction of RDT/ACT in a catchment area of a health center in East Sepik Province, PNG. We interviewed caregivers with children less than 15 years of age and collected data on fever episodes in the preceding 2 weeks. Using propensity score matching, febrile children before the introduction of RDT/ACT were matched to febrile children after the introduction. Then, the adjusted difference in the proportion of health service utilization (i.e., the average treatment effect [ATE] of the introduction of RDT/ACT on health service utilization) was estimated. We also employed a multilevel Poisson regression model to investigate factors influencing the use of health services. Results: Of 4690 children, 911 (19%) were reported to have a fever episode. The unadjusted proportion of health service utilization was 51.7% and 57.2% before and after the RDT/ACT introduction, respectively. After matching, no significant difference in the health service utilization was observed before and after the introduction of RDT/ACT (ATE: 0.063, 95% confidence interval −0.024 to 0.150). Multilevel regression analysis showed that the consistent factors associated with a higher utilization of health services were severe illness and being female. Conclusion: The utilization of health services was not significantly different before and after the introduction of RDT/ACT. Villagers may have neither sufficient information on the new protocol nor high acceptance of RDT/ACT. The observed gender bias in health service utilization could be due to female caregivers’ preferences toward girls.